Multidisciplinary Information Retrieval Second Information Retrieval Facility Conference, IRFC 2011, Vienna, Austria, June 6, 2011, Proceedings - Hanbury, Allan.; Hanbury, Allan.; Rauber, Andreas.; Rauber, Andreas.; De Vries, Arjen.; De Vries, Arjen. (Information Systems and Applications, incl. Internet/Web, and HCI, 2011)
This book constitutes the proceedings of the Second Information Retrieval Facility Conference, IRFC 2011, held in Vienna, Austria, in June 2011. The 10 papers presented together with a keynote talk were carefully reviewed and selected from 19 high-quality submissions. IRF conferences wish to bring young researchers into contact with industry at an early stage. The second conference aimed to tackle four complementary research areas: information retrieval, semantic web technologies for IR, natural language processing for IR, and large-scale or distributed computing for the above areas. The papers are organized into topical sections on patents and multilinguality, interactive retrieval support, and IR and the Net.